A Novel Approach to Signal Encryption: Improved Version of Conventional DSSS Scheme - -, Mohd Abdur Rashid; Mohamed, Saiful Bahri; -, A. Hiral; -, N. Sakibr (2011)
Cryptography is the art of information hiding and verification to ensure precise security facility of the signal. It entirely deals with protocols, algorithms and strategies to securely and consistently avert unauthorized access to confidential information. In most of the encryption scheme, some difficulties may arise such as complexity either in encryption or decryption, expansion in required bandwidth etc. In this proposal; an audio signal is suggested to be encrypted using sample by sample method instead of bit by bit encryption of direct sequence spread spectrum_ After sampling of a signal, simple mathematical operation is performed in each sample with a time varying arbitrary weights. This arbitrary weight can be obtained from DIA conversion of pseudo noise sequence. Et is evident that, the encrypted samples are largely deviated than the origin which literally ensures much efficient encryption scheme.